PENGARUH KOLABORASI PBL DENGAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PADA PEMBELAJARAN EKONOMI KELAS X SMA KARTIKATAMA METRO LAMPUNG - Irmawati, Effy; Martono, Trisno; Murtini, Wiedy (Department of Economics Education, Universitas Sebelas Maret, 2017)
This study aims to find out : (1) students' learning outcome before the collaboration of PBL instractional model and STAD cooperative instructional model being applied for 10th grade students of SMA Kartikatama Metro ;(2) students' learning outcome after the application of the method and technique;(3) the influence of collaboration application of PBL instructional model and STAD cooperatice instructional model. This was quantitative research with a quasi-experimental design. Application of PBL teaching method collaborated with STAD cooperative instructional model is able to improve students' learning outcome and give significant influence towards the improvement of students' learning outcome at economics subject. Compared to the class X-A of social program that only applies PBL instructional model, class X-D is better in case of learning outcome improvement. Given that the result of pre-test, class X-A and X-D get 46.3 and 51.4 respectively. Those two scores are categorized into less than or far from the Minimum Mastery Criteria (KBM) by 75. But, after the implementation of PBL instructional model and STAD cooperative instructional model, outcome learning rises. The result of learnig outcome of those two classes shows that class X-A gets 68.04 while class X-D gets 80. Those two learning outcomes indicate a significant difference on students' learning outcome in economics subject.